(3eaGgje CSGSjI aj Yde GdGbJUGO (B: (3GdGbJUGO Gdcdj s - (3GSeGYjd(B, (3YHO GdQMef s; (3MQHj eMeO ehSi YQjbGJ(B, s ((3YeGf(B:s (3OGQ hGFd ddWHGYI hGdfTQ(B,s, 1999)
(3WHjYI Yde GdGbJUGO h MSGHGJ GdONd Gdbhej h fXQjI GdGSJgdGc h JNWjW GdGSJKeGQ h fXQjI GdGONGQ h GdHWGdI h GdJVNe h GdSjGSI GdeGdjI h GdfbhO h GdeUGQa h GdJLGQI GdNGQLjI h ejRGf GdeOahYGJ h GdJfejI GdGbJUGOjI h Gdfeh GdGbJUGOj h cOG GdJNWjW GdGbJUGOj h CNjQG GdJcGed GdGbJUGOj(B.s
(3eQGLY U(B.489s
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdLRFjs